Gastrointestinal disorders associated with migraine: A comprehensive review - Camara Lemarroy, Carlos Rodrigo; Rodríguez Gutiérrez, René; Monreal Robles, Roberto; Marfil Rivera, Alejandro (WJG Press, 2016)
Migraine is a recurrent and commonly disabling primary headache disorder that affects over 17% of women and 5%-8% of men. Migraine susceptibility is multifactorial with genetic, hormonal and environmental factors all playing an important role. The physiopathology of migraine is complex and still not fully understood. Many different neuropeptides, neurotransmitters and brain pathways have been implicated. In connection with the myriad mechanisms and pathways implicated in migraine, a variety of multisystemic comorbidities (e.g., cardiovascular, psychiatric and other neurological conditions) have been found to be closely associated with migraine. Recent reports demonstrate an increased frequency of gastrointestinal (GI) disorders in patients with migraine compared with the general population. Helicobacter pylori infection, irritable bowel syndrome, gastroparesis, hepatobiliary disorders, celiac disease and alterations in the microbiota have been linked to the occurrence of migraine. Several mechanisms involving the gut-brain axis, such as a chronic inflammatory response with inflammatory and vasoactive mediators passing to the circulatory system, intestinal microbiota modulation of the enteric immunological milieu and dysfunction of the autonomic and enteric nervous system, have been postulated to explain these associations. However, the precise mechanisms and pathways related to the gut-brain axis in migraine need to be fully elucidated. In this review, we survey the available literature linking migraine with GI disorders. We discuss the possible physiopathological mechanisms, and clinical implications as well as several future areas of interest for research.